Beban Kerja Yang Berat Menyebabkan Ketidakpatuhan Perawat Dalam Melengkapi Pendokumentasian: The Heavy workload That Causes Nurse Disobedience in Completing Documentation - Wahyuni, Rini (Dohara POAJ, 2022)
Introduction: In every implementation of the nursing process, nurses will always record or often called documenting. Documenting is an activity of recording, reporting, or recording an event and activity carried out in the form of providing services that are considered important and valuable. One of the factors that can affect documenting is workload. The workload of a nurse can be seen as the dimension of all activities or activities carried out by a nurse during a stint in a nursing service unit. Methods: This type of research uses quantitative descriptive assessments using the Chi-Square method and samples taken by 79 nurses. The independent variable uses a Questionnaire instrument and the dependent variable uses an observation sheet where the questionnaire has 13 questions from Nursalam in 2017 and the observation sheet has 24 questions from the Depkes RI in 1995. Results: It was obtained that 29 out of 43 respondents (67.4%) stated heavy workload with non-compliance levels and 32 out of 36 respondents (88.9%) stated light workload with compliance levels. Statistical test results obtained the value of P-value = 0.000 means p-value < (0.05). Discussion: There is a workload relationship with the level of compliance of nurses in completing the documenting of nursing care in the RSPAD surgical room in 2021.